2012
DOI: 10.1177/1753193412452080
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound changes in the extensor pollicis longus and flexor pollicis longus tendons following open reduction and internal fixation of displaced intra-articular fractures of the distal radius

Abstract: A previous ultrasound study showed inflammation around the extensor pollicis longus tendon and surrounding structures at 6 weeks after manipulation, with or without pin fixation, and immobilization for distal radius fracture. Ultrasound examination after plating of distal radius fracture followed by early active mobilization of the wrist showed a short-lived inflammatory response, evident at 2 weeks but not at 6 weeks, around the extensor pollicis longus tendon (26 wrists examined) and flexor pollicis longus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Intra- and postoperative usage of high-frequency ultrasound in musculoskeletal trauma is a relatively new method for various purposes. [ 10 , 11 ] Recently, few authors have reported good initial results with sonography in different musculoskeletal operations. [ 12 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Intra- and postoperative usage of high-frequency ultrasound in musculoskeletal trauma is a relatively new method for various purposes. [ 10 , 11 ] Recently, few authors have reported good initial results with sonography in different musculoskeletal operations. [ 12 , 13 ]…”
Section: Discussionmentioning
confidence: 99%